Experimental And Finite Element Analysis Of Contact Behavior In Lubricated Rolling Contact - Yap, Jun Heng (Universiti Sains Malaysia, 2021)
Lubricants such as oil and grease are widely used in rolling element bearings to reduce the friction between two metal surfaces. Lubricant forms a thin film between the surfaces to partially sustain the load exerted by the bearings. Improper lubrication may cause high contact stress and deformation to the bearings and will eventually lead to catastrophic failure. The purpose of this project is to investigate the coefficient of friction produced by newly developed palm oil-based grease and to investigate the contact characteristics in lubricated roller bearings by finite element analysis. The result is then compared with two available commercial greases to evaluate the performance. There were four types of grease that were tested experimentally, which were palm oil-based grease formulations A and B, food grade grease and mineral grease. The respective friction coefficients were determined using four-ball tester following the standard testing procedure ASTM D2266. The finite element analysis of 2D and 3D partial roller bearing models were conducted in static condition using the ANSYS simulation software. The finite element model is developed based on the roller bearing geometry and the simulation is carried in a frictionless and lubricated condition. The finding shows that palm oil grease formulation A had the least coefficient of friction, followed by palm oil grease formulation B, mineral grease and food grade grease. This indicates that the palm oil-based grease has the potential to be applied in rolling contact applications due to low friction characteristics. Finite element analysis with various lubricant coefficients of friction shows that the maximum von Mises stress and total deformation for frictional contact are higher than the frictionless contact. For the 2D friction contact analysis, similar values were obtained with von Mises stress at 400.69 MPa and deformation at 3.4033×10-4 mm. Meanwhile, for 3D partial roller bearing model, the results showed there was a slightly decreasing trend on the equivalent stress and total deformation between the roller and the inner ring with the increase in the coefficient of friction of the grease. The results were compared with the analytical method based on Hertzian Contact Theory, where the values of equivalent stress and total deformation for frictionless contact using 2D method were closer to the theoretical values than that using 3D method. The finding shows that the small difference in grease coefficient of friction did not affect the rolling contact. The finding also shows that the newly developed biodegradable grease has a similar performance in terms of rolling contact friction and contact characteristic in a condition that the bearing is operating in normal condition.